Avaliação das condições de tratamento de esgoto a partir do emprego de modelo de qualidade de água, técnica de otimização e análise multicritério – estudo de caso da bacia hidrográfica do Rio Novo, Espírito Santo - Spagnol, Izabela Tavares (2023)
The improper disposal of domestic and industrial effluents is the main source of water pollution in Brazil. In this context, sewage treatment before discharge is usually the primary pollution control strategy. The selection of treatment technologies requires a comprehensive analysis of environmental, technological, operational, and social factors associated with treatment systems, along with the assessment of the supporting capacity of watercourses that will receive the final disposal of sewage. In this perspective, this study aims to investigate the conditions of domestic sewage treatment in the Rio Novo watershed, in the state of Espírito Santo, using a Decision Support System (SSD) consolidated through the combination of a water quality simulation model, optimization technique, and Multicriteria Analysis. For the study area, the parameters BOD5,20 and thermotolerant coliforms emerged as the most relevant for potential selections of sewage treatment technologies. The district of Itaipava, lacking operational sewage treatment systems, exhibited significant minimum removal efficiencies for the parameters DBO5,20, thermotolerant coliforms, and phosphorus in all evaluated scenarios. In the combined analysis of DBO5,20 and thermotolerant coliforms, the Monte Belo and Duas Barras Sewage Treatment Plants (ETEs) required minimally relevant removal efficiencies for both parameters, despite having operational sewage treatment stations. The use of an optimization model based on equity measures expanded treatment efforts within the study area. Additionally, the expansion of the pollutant set for the pre-selection process of technologies restricted the set of alternatives to be prioritized in the Multicriteria Analysis. Regarding the set of alternatives indicated in the SSD for the watershed, variations in stabilization pond systems and activated sludge processes constituted technologies that consistently appeared as the most suitable at the end of the multicriteria analysis.